Severe parkinsonism under treatment with antipsychotic drugs - Druschky, Katrin; Bleich, Stefan; Grohmann, Renate; Engel, Rolf R.; Toto, Sermin; Neyazi, Alexandra; Däubl, Barbara; Stübner, Susanne (European archives of psychiatry and clinical neuroscience, 2019)
The aim of the study was to assess rates of severe parkinsonism related to different antipsychotic drugs (APDs) using data from an observational pharmacovigilance programme in German-speaking countries—Arzneimittelsicherheit in der Psychiatrie (AMSP). Data on APD utilization and reports of severe APD-induced parkinsonism were collected in 99 psychiatric hospitals in Austria, Germany and Switzerland during the period 2001–2016. Of 340,099 patients under surveillance, 245,958 patients were treated with APDs for the main indications of schizophrenic disorders, depression, mania and organic mental disorders. A total of 200 events of severe APD-induced parkinsonism were identified (0.08%). First-generation low-potency APDs were significantly less often implicated (0.02%) than second-generation APDs (0.07%) and first-generation high-potency APDs (0.16%). Among the second-generation APDs, amisulpride and risperidone ranked highest. The phenothiazines were associated with significantly lower rates of severe parkinsonism (0.02%) than those of the butyrophenones (0.11%) and thioxanthenes (0.12%). In 71 cases (35.5%), more than 1 drug was considered responsible for the induction of severe parkinsonism. In 44 patients (22.0%), the symptoms were extremely severe, leading to complete immobility and/or massive complications such as pneumonia and severe injuries due to falls. Higher age (> 60 years) was associated with significantly higher rates of severe parkinsonism, as were the diagnoses of schizophrenic disorder or mania. The large number of patients included in the present survey allows for the comparison of severe parkinsonism rates related to different APD classes and single APDs. The first-generation low-potency APDs had significantly reduced risk of severe parkinsonism compared not only to high potency but also to second-generation APDs.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Adverse drug reactions; AMSP programme; Antipsychotic drugs; Psychiatric inpatients; Severe parkinsonism